Answer:
1
the equation (x-4)^2-17=8 has two solutions because it is in a quadratic form.
(x-4)^2-17=8
x²-8x+16-17-8=0
x²-8x-9=0
Doing middle term factorization
x²-9x+x-9=0
x(x-9)+1(x-9)=0
(x-9)(x+1)=0
either
x=9
x=9or
x=9orx=-1
2.
x^2+4x+3=0:
Doing middle term factorization
x²+3x+x+3=0
x(x+3)+1(x+3)=0
(x+3)(x+1)=0
either
x=-3
or
x=-1
Josh’s solution is incorrect because he missed x=-3.
3.
x^2-6x+7=0
By using quadratic equation formula:
Comparing above equation with ax²+bx+c=0
we get
a=1
b=-6
c=7
Now
we have
x=[tex] \frac{ - b ± \sqrt{ {b}^{2} - 4ac} }{2a} [/tex]
x=[tex] \frac{ 6± \sqrt{ {-6}^{2} - 4*1*7} }{2} [/tex]
x=[tex] \frac{ 6±2\sqrt{ 2}}{2} [/tex]
x=[tex] { 3±\sqrt{ 2}} [/tex]
Taking positive
x=[tex] { 3+\sqrt{ 2}} [/tex]
taking negative
x=[tex] { 3-\sqrt{ 2}} [/tex]